Two Different Methods of Oral Mucocele Management in Pediatric Patients : A Case Report - Katta, Nandini; KM, Sudheesh; Arekal, Shruthi (UI Scholars Hub, 2018)
Mucoceles are considered to be the most common oral lesion, with an approximate prevalence of around 2.4 cases per 1,000 people. The exact prevalence in children is not reported, but they are thought to occur more frequently in younger individuals when compared to adults. The age old treatment for mucocele involves surgical excision, which is associated with mental trauma and discomfort to the patient. Other treatment options that can be considered include cryosurgery, CO2 laser ablation, micro marsupialization, intralesional corticosteroid injection, marsupialization and electrocautery. Cryosurgery is the procedure where there is deliberate destruction of tissue by freezing, using liquid nitrogen. This treatment is well received by patients, as minimal or no local anesthesia is used, relative lack of discomfort, no bleeding and minimal to no scarring after healing. This paper presents two cases of oral mucocele treated by surgical excision and cryosurgery. The procedures and the results of the two treatment are presented and discussed.